Strategic/Sectoral, Social and Environmental Assessment of Power Development Options in the Nile Equatorial Lakes Region : Appendices - SNC Lavalin International (World Bank, Washington, DC, 2014)
The strategic / sectoral social and environmental assessment of power development options (SSEA) offers an overview analysis of major regional power development options and regional transmission interconnections in the Nile Equatorial Lakes region in Eastern Africa. The assessment provides a solid foundation for planning the development of the power sectors of the region as it contains a proposed development strategy and a regional Nile Equatorial Lakes indicative development plan to the year 2020. The SSEA is based on a review of the current environmental and social context, the existing legal and regulatory framework, an assessment of the power needs for the region, and identification of the power development options and a comparison of these options in terms of environmental, socio/economic and risk considerations. It is a tool for public and private financiers, in their assessment of potential support to power development programs and projects in the region from a strategic perspective. The SSEA is consistent with the World Bank's 2001 Environment Strategy and was undertaken within the framework of the Nile Basin Initiative (NBI) and the Nile Equatorial Lakes Subsidiary Action Program, one of two investment sub-programs of the NBI, promoting cooperative investment projects in Eastern Africa. The study area covered Burundi, the eastern region of the Democratic Republic of Congo, Rwanda, Kenya, Tanzania and Uganda and was undertaken in partnership with country experts and regional stakeholders. Key recommendations include: a) a set of power options to be implemented as soon as possible; b) further baseline studies of promising power options; c) countries in the region should move towards a high degree of power system interconnection and associated legal reforms; and d) prepare, develop and finance in the order of 100 MW of identified priority power options and strengthen the associated transmission networks.